Teachers Competency in Test Construction in Secondary Schools in Ovia North-East Local Government Area Edo State - ADEOSUN, Praise Kehinde; MOGOKWU, Gods’Time (Ilorin Journal of Education, 2024)
The study investigated teachers’ competency in test construction in senior secondary schools in Ovia North- East local government area of Edo state. The descriptive survey design was adopted for the study. The study population comprised 162 teachers in the 23 senior secondary schools in Ovia North-East local government area of Edo state. The sample of the study consists of all 162 teachers in the senior secondary schools. The census method was used because the entire population of the study were used. The research instrument used for data collection was the Teachers’ Competency in Test Construction Questionnaire (TCTCQ). The instrument was validated by three experts. Reliability of the instrument was done using the Cronbach alpha method, and a coefficient of 0.80 was obtained. The research question was answered using descriptive statistics such as mean and standard deviation while hypotheses were tested using the independent t-test and analysis of variance (ANOVA). The results revealed that the teachers in Ovia North-East Local Government Area of Edo state, have high competency in test construction. It was also found that a significant difference exists among the teachers in the area of competency in test construction based on sex. However, no significant differences were found among the teachers’ competency in test construction based on qualification and years of experience of teachers. It was recommended that, periodic workshops for teachers to keep them abreast of new developments in the area of test construction to sustain this level of competency.